Psychodrama and Spirituality: A Practice-Friendly Review - Gökhan Özcan (Spiritual Psychology and Counseling)
Psychodrama is a set of widely-used philosophy, theories, and techniques on which J. L. Moreno laid the foundations. Moreno built his philosophy and practice on spiritual grounds from existential thought, theology, and texts about the relationship between God and man. This article aims to summarize the definition, basic process, and techniques of psychodrama, a group of psychotherapy methods, to reveal the relationship between Moreno philosophy and spirituality in different aspects and to examine Jungian Psychodrama, Souldrama, and the Therapeutic Spiral Model in this context as contemporary spiritually oriented psychodrama approaches.